Multiple Sclerosis Presenting with Parsonage–Turner Syndrome: A Case Report. Issue 4 (December 2013) - Duman, Iltekin; Guvenc, Inanc; Tezel, Kutay; Aydemir, Koray
Abstract Background: A case of Parsonage–Turner syndrome [PTS] with typical sudden onset of shoulder pain and weakness in shoulder girdle was presented. Findings: Electrodiagnostic testing revealed an upper trunk lesion. Further diagnostic steps were pursued because of medical history and additional clinical findings. Hyperintense plaques typical of multiple sclerosis [MS] were revealed by cranial magnetic resonance imaging. Diagnosis of clinically definite MS was establised according to the McDonald criteria. Conclusions: A variety of peripheral nervous system pathologies might coexist with MS with unknown binding pathogenesis. This is an unusual case of PTS coexisting with MS as the presenting symptom.